Toward the measurement of multiple fluorescence lifetimes in flow cytometry: maximizing multi‐harmonic content from cells and microspheres. Issue 11 (26th February 2015) - Jenkins, Patrick; Naivar, Mark A.; Houston, Jessica P.
Abstract : Flow cytometry is a powerful means for in vitro cellular analyses where multi‐fluorescence and multi‐angle light scattering can indicate unique biochemical or morphological features of single cells. Yet, to date, flow cytometry systems have lacked the ability to capture complex fluorescence dynamics due to the transient nature of flowing cells. In this contribution we introduce a simple approach for measuring multiple fluorescence lifetimes from a single cytometric event. We leverage square wave modulation, Fourier analysis, and high frequency digitization and show the ability to resolve more than one fluorescence lifetime from fluorescently‐labelled cells and microspheres.Illustration of a flow cytometer capable of capturing multiple fluorescence lifetime measurements; creating potential for multi‐parametric, time‐resolved signals to be captured for every color channel. Abstract : In this contribution fluorescence decay‐dependent parameters to the data space of flow cytometry are introduced. A stream‐in‐air FACS™ instrument is modified with new laser modulation hardware and a data acquisition system that could be readily adapted onto other cytometers when there is a need to capture the fluorescence lifetime, which is an intensity‐independent parameter. Using square wave modulation, the ability to resolve more than one fluorescence lifetime from individual fluorescently labeled cells and microspheres that are counted at rapid cytometric throughputs is shown.Illustration of a flow cytometer that captures more than one average fluorescence lifetime per channel. This image depicts the potential for a single cytometer to be expanded such that time‐resolved signals that are multi‐parametric can be obtained for every color channel . The ability to rapidly collect multiple fluorescence lifetimes from each emission detector is a powerful technique for single cell analysis and sorting.